"Busuk dan Jijik Perbuatan Mereka":: Orientasi Religius dan Emosi Jijik pada Dewasa Muda di Jabodetabek - Laura Precious Bless; Karel Karsten Himawan (Societas Dei: Jurnal Agama dan Masyarakat, 2025)
Religious beliefs are often intertwined with emotional responses, particularly toward stimuli perceived as impure or morally deviant. The way individuals internalize religious teachings may shape how they experience emotions like disgust. This study examined the influence of religious orientation–both intrinsic and extrinsic– on disgust sensitivity among adults in the Greater Jakarta area. To explore this, 375 participants (Mage = 32.18, SD = 2.82) were recruited using snowball and purposive sampling methods and completed an online survey. Religious orientation was measured using the Religious Orientation Scale (ROS), while disgust sensitivity was assessed with the Three Domains of Disgust Scale (TDDS). Analysis revealed that extrinsic religious orientation significantly predicted higher levels of disgust sensitivity, and this relationship was more pronounced among women. These findings suggest that individuals who approach religion for instrumental or social purposes may exhibit heightened emotional reactivity to disgust-related stimuli, with gender differences indicating a potentially stronger sensitivity among women.